PENGENALAN TEKNIK DASAR OVERHAUL MESIN PISTON PESAWAT UDARA TIPE OPPOSED UNTUK GURU SMK PENERBANGAN - Wira Ghautama; Djoko Herwanto; Lilies Esthi Riyanti; Mursyidin Mursyidin; Andri Kurniawan (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Penerbangan Palembang, 2021)
This training activity was motivated by the low number and competence of teachers in the productive field of aviation vocational high schools. Government data for 2019 shows that the majority of teaching staff postures are still dominated by the category of adaptive normative fields or general teachers, while productive teachers who teach subject matter according to their fields of expertise are still low, at a percentage below 35%. The aim of the training is to introduce the basic technique of overhauling opposed type aircraft piston engines for teachers of Aviation Vocational Schools. As a form of community service responsibility, lecturers provide training in the form of a basic introduction to piston engine overhaul so that productive teachers can have an understanding and skill in piston engine maintenance using standard tools. With the location of the activity at SMKN 12 Bandung which has a major in Airframe and Powerplant. The method of this activity begins with briefing on the concept of overhaul, introduction to the use of standard tools, regulations and how to read manuals and other manufacturing technical publications. After the participants have basic mastery of the concept, the activity continues with the introduction of piston engine parts and top end overhaul training in accordance with the training objectives. As a result of this training, teachers already have the understanding and overhaul skills of aircraft piston engines that are in accordance with the manufacture manual so that they can improve the teaching quality of productive fields.